Broadband access in Japan rapidly growing FTTH market. - Shinohara, Hiromichi (IEEE Communications magazine)
This article describes the latest FTTH technologies and market developments in Japan today. It focuses in particular on FTTH services, the deployment of FTTH systems, and lessons learned from actual deployments. The article also discusses the key R&D issues that must be completed if we are to enter the full-scale FTTH era.